Burnout Among US Military Behavioral Health Providers. Issue 6 (June 2018) - Stearns, Shaun; Shoji, Kotaro; Benight, Charles C.
Abstract : Abstract: The present study investigated the prevalence of burnout among US military behavioral health providers (BHPs) and tested a mechanism of developing burnout in a job demands–resources model. Surveys were sent to BHPs working with US military populations globally (T1). Six months after, surveys were collected again at T2. In total, 271 providers completed T1, and 116 completed T2. The job demands–resources model showed that T1 burnout self-efficacy and support predicted T2 burnout and work engagement. T1 job demands predicted T2 burnout. To provide a deeper comparison of our findings, we included a meta-analysis, which indicated burnout among BHPs working on a military installation was equivalent with other professions. Providers working with military clients within the community reported lower burnout than other professionals. Findings suggest BHPs working on a military installation might be at greater risk of developing burnout. Burnout might be preventable by increasing job resources and decreasing job demands.